EFEKTIVITAS PEMBELAJARAN INFORMATIKA BERBASIS PRAKTIK DALAM PENGENALAN SISTEM KOMPUTER PADA SISWA KELAS IX DI SMPN 1 GALESONG SELATAN - Nurhidayani; Azzahra, Andi; Ardiana; Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology (ICT) in the digital era requires educational institutions to equip students with digital literacy from an early age. One subject that plays a strategic role in developing these competencies is Informatics. However, Informatics learning at the junior high school level still tends to be theoretical and lacks direct practical activities, resulting in suboptimal student understanding of computer systems. This study aims to examine the effectiveness of practice-based Informatics learning on the learning outcomes of Grade IX students at SMPN 1 Galesong Selatan, as well as to describe student activities and responses to the implementation of this learning method. The study employed a quantitative approach using a pre-experimental design (One Group Pretest–Posttest Design) involving 23 students as research subjects. The results showed that the average pretest score of 76.25 increased to 87.91 in the posttest. A paired-sample t-test revealed that the calculated t-value (4.23) was greater than the t-table value (2.00), indicating a significant improvement in learning outcomes after the implementation of practice-based learning. Furthermore, 92% of students responded positively, suggesting that this method enhanced student engagement, motivation, and understanding of introductory computer systems material. Therefore, practice-based Informatics learning has proven effective in improving student learning outcomes.